ROLE OF COOPERATION IN THE IMPROVEMENT OF THE AGRICULTURAL ECONOMY - Melva Sitanggang (Proceeding International Conference on Information Technology and Business, 2015)
Indonesia is an agricultural country rich innatural resources and livelihood of theIndonesian population of predominantlyagricultural products. In the development of theagricultural economy caused by a problem in thefield of agriculture as well as in the availabilityof venture capital that will be used by farmers inthe provision of seeds and fertilizer as well asmaintenance until production is required for therole of cooperatives in alleviating bebab offarmers.According to the Act - Act No. 25 in 1992, saidthat